The Post-genomic Era of Trichoderma reesei: What's Next?. Issue 12 (December 2016) - Gupta, Vijai Kumar; Steindorff, Andrei Stecca; de Paula, Renato Graciano; Silva-Rocha, Rafael; Mach-Aigner, Astrid R.; Mach, Robert L.; Silva, Roberto N.
Abstract : The ascomycete Trichoderma reesei is one of the most well studied cellulolytic microorganisms. This fungus is widely used in the biotechnology industry, mainly in the production of biofuels. Due to its importance, its genome was sequenced in 2008, opening new avenues to study this microorganism. In this 'post-genomic' era, a transcriptomic and proteomic era has emerged. Here, we present an overview of new findings in the gene expression regulation network of T. reesei . We also discuss new rational strategies to obtain mutants that produce hydrolytic enzymes with a higher yield, using metabolic engineering. Finally, we present how synthetic biology strategies can be used to create engineered promoters to efficiently synthesize enzymes for biomass degradation to produce bioethanol. Trends: Synthetic construction of regulatory elements such as transcriptional factors and promoters for T. reesei expands the toolbox for fungal engineering. The identification of novel cis -regulatory elements using systems biology approaches has begun to provide building blocks for constructing complex circuits in T. reesei . The use of synthetic biology standards, such as the BioBricks assembly format, for constructing modular systems for T. reesei has been reported, and its generalization should have a strong impact in the field. While the simultaneous implementation of multiple expression systems in T. reesei has been reported, there is still a pressing need to develop novel tools and techniques that could provide an efficient strain engineering platform for this organism.